MENAIKKAN KESADARAN MASYARAKAT DI DADAPAN TERHADAP BERITA HOAKS PADA MASA PANDEMI - Iden Bardan Bayunugraha (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2021)
The rapid development of digital media is in line with the fast and large amount of information and news that is obtained by the public. The news that spreads can be fake news or hoaxes. This hoax itself can shake the view of the reader which is finally able to cause different views, divisions, and commotion in the community. Hoaxes regarding Covid-19 and vaccinations certainly play a very large role in the implementation of preventing Covid-19 from being hampered or even failing. Reflecting on this, it is necessary to socialize digital literacy as a form of education about the nature of tabayyun. This research was conducted in Dadapan, Wonokerto, Turi, Sleman with the aim of seeing how the impact of socialization on public awareness of the news from digital media that they read. Qualitative research with narrative data analysis was carried out and produced data that there was a change in people's behavior from before the socialization was given, namely those who initially did not comply with health protocols to become concerned and responsive in suppressing the spread of Covid-19 by implementing health protocols.